Management of Patients Using Combination Therapy With Pioglitazone and a Dipeptidyl Peptidase-4 Inhibitor: An Analysis of Initial Versus Sequential Combination Therapy. Issue 3 (May 2014) - Bron, Morgan; Ayyagari, Rajeev; Sharma, Hari; Chen, Kristina; Bozas, Ana; Wu, Eric
Abstract : : Current type 2 diabetes mellitus (T2DM) treatment involves progressive interventions from lifestyle changes to pharmacological therapies. Previous studies found that combination therapy with a dipeptidyl peptidase-4 inhibitor (DPP-4i) and pioglitazone (PIO) is more effective than monotherapies in treating poorly controlled T2DM, but there is no consensus on whether these drugs should be initiated at the same time (initial combination therapy) or sequentially. We aimed to assess glycemic control with initial versus sequential combination therapy with PIO and a DPP-4i in patients with glycosylated hemoglobin (HbA1c ) levels ≥ 7%. A retrospective chart review was conducted on T2DM patients from diverse geographic sites in the United States initiating therapies from March 2, 2010 to February 28, 2011. Patients were selected for initial combination therapy, if starting PIO and a DPP-4i within 30 days of each other, or sequential combination therapy, if first taking PIO alone for ≥ 60 days before adding a DPP-4i within 1 year of PIO initiation. The HbA1c level reduction from baseline was compared between cohorts using linear regression models adjusting for demographics, baseline HbA1c, T2DM duration, comorbidities, and various medications. There were 250 patients in the initial and 211 in the sequential combination therapy cohorts; 57.3% were male, 65.3% were Caucasian, and the mean age was 54.3 years. Patients receiving initial combination therapy had a significantly higher mean baseline HbA1c level (8.6% vs 8.0%, P < 0.0001), a higher prevalence of coronary artery disease (11.6% vs 6.2%, P = 0.0430), and a lower prevalence of hyperlipidemia (56.4% vs 67.8%, P = 0.0120) and of hypertension (62.4% vs 72.0%, P = 0.0290), compared with the sequential therapy cohort. In adjusted analyses, initial combination therapy was associated with a significantly greater reduction in HbA1c levels than sequential combination therapy at months 12, 16, and 20 (−0.977 vs −0.819, P = 0.034; −1.453 vs −1.242, P = 0.048; and −1.182 vs −0.810, P = 0.013, respectively). Our findings suggest initial combination therapy may be the preferred option in choosing combination therapies.